2007
DOI: 10.1039/b617576g
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on aromatic stacking interactions

Abstract: Synthetic supramolecular zipper complexes have been used to quantify substituent effects on the free energies of aromatic stacking interactions. The conformational properties of the complexes have been characterised using NMR spectroscopy in CDCl(3), and by comparison with the solid state structures of model compounds. The structural similarity of the complexes makes it possible to apply the double mutant cycle method to evaluate the magnitudes of 24 different aromatic stacking interactions. The major trends i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
220
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(245 citation statements)
references
References 83 publications
18
220
1
6
Order By: Relevance
“…If, however, the interacting molecules are non-rigid or contain bulky side chains comparable in their dimension with the aromatic chromophore, the disruption of the compact π-stacking structure may occur as was clearly shown in dye-dye hetero-complexes [219]. It is difficult to ascertain whether in this context the principle of 'structural complementarity' must be supplemented by 'electrostatic complementarity' recently introduced for aromatic interactions [36], as differentiation of their influence on hetero-association is not possible with the data available. However, there is direct NMR evidence for the formation of two dimer structures of the antibiotic DAU with either parallel (charges on DAU aminosugar are in close proximity to each other) or antiparallel (charges on DAU aminosugar are well separated) orientations of chromophores [221,222], which suggests that electrostatic factor may not be so significant in aqueous solution.…”
Section: Hetero-association Of Aromatic Drugs With Aromatic Mutagens mentioning
confidence: 99%
See 1 more Smart Citation
“…If, however, the interacting molecules are non-rigid or contain bulky side chains comparable in their dimension with the aromatic chromophore, the disruption of the compact π-stacking structure may occur as was clearly shown in dye-dye hetero-complexes [219]. It is difficult to ascertain whether in this context the principle of 'structural complementarity' must be supplemented by 'electrostatic complementarity' recently introduced for aromatic interactions [36], as differentiation of their influence on hetero-association is not possible with the data available. However, there is direct NMR evidence for the formation of two dimer structures of the antibiotic DAU with either parallel (charges on DAU aminosugar are in close proximity to each other) or antiparallel (charges on DAU aminosugar are well separated) orientations of chromophores [221,222], which suggests that electrostatic factor may not be so significant in aqueous solution.…”
Section: Hetero-association Of Aromatic Drugs With Aromatic Mutagens mentioning
confidence: 99%
“…The hetero-association of specially selected (synthesised) aromatic molecules has been used as a model system to provide insight into various processes of particular importance in chemistry, such as 4 M.P. Evstigneev arrangement of nucleic acid bases derivatives in stacked complexes [23,30], binding of drugs to nucleic acids [31] and aromatic residues of proteins [32,33], protein-DNA and protein-protein interactions [3,34], exciton and charge-transfer interactions [25,34,35], dye chemistry [22], electrostatic complementarity [12,36], and 'energetic composition' of π-stacking [3,8,37]. (2) Biochemical applications.…”
Section: Applications Of Hetero-associationmentioning
confidence: 99%
“…3 Some studies have already shown the impact of the electronic properties of the substituents on the stability of these interactions in ligand−receptor binding. 4,5 Therefore, by increasing the electronic density with an electron-donating group, we expected to reinforce the interaction between the distal benzene ring and the Phe 6.52 residue.…”
mentioning
confidence: 99%
“…A series of Diels-Alder adducts of resin acid with acrylic acid were synthesized, and these showed great antimicrobial activity against different kinds of bacteria by filter paper method (Li et al 2012;Wang et al 2012). It was also reported that aromatic constituents of compounds had broad spectrum anti-fungal activity (Cockroft et al 2007;Pattnaik et al 1997). As an inexpensive natural product, fungicides related to rosin have superiority.…”
Section: Introductionmentioning
confidence: 99%